A bibliometric analysis of the development of autonomous ships in inland waterway transport - Xue, Jie; Li, Qianbing; Song, Yuanming; Yang, Peijie; Feng, Yuanjun; Hu, Hao (Frontiers in Marine Science, 2025)
Inland waterway transport (IWT) plays a critical role in global logistics, offering large-capacity, long-distance transport at a lower cost. Recently, the advent of autonomous ships has promised to revolutionize efficiency and sustainability within the shipping industry. While existing research predominantly targets maritime settings, the distinct challenges of inland waterways such as fluctuating water depths, varying river currents, and confined channels demand tailored technological solutions. This study provides a thorough bibliometric analysis of autonomous ships in inland waterway transport, based on 163 publications from the Web of Science (WoS) core collection. This study identifies key technological milestones in this field and highlights the research gaps of adapting maritime autonomous ship technologies to inland waterways. The pressing need for customized solutions is also discussed. By reviewing the current landscape, this study contributes to the field as a beneficial reference for researchers, industry professionals, and policymakers, promoting the development of autonomous ship technology in inland waterways.